(untitled) (UNED Research Journal, 2021)
Introduction: The nutritional analysis of commercial food helps optimize its use and the pets’ nutrition, and there are no recent analyses of this type for Costa Rica. Objective: To recommend pet foods according to the physiological state, level of activity and weight of cats and dogs in Costa Rica. Methods: Products registered at the government’s Directorate for Animal Food were analyzed for nutritional information (2017) and animal requirements using three equations for cats and nine for dogs. Results: Of the average package recommendations, 71% would provide insufficient nutrition for dogs, and 63% insufficient nutrition for cats. Conclusions: Most commercial food products available in Costa Rica recommend amounts that are insufficient to meet the needs of many cats and dogs.